A 5 degrees of freedom multi-user pointing device for interactive whiteboards. Issue 1 (February 2016) - Albarelli, Andrea; Cosmo, Luca; Bergamasco, Filippo; Sartoretto, Flavio; Torsello, Andrea
Abstract Interactive whiteboards are nowadays rather common equipments in classrooms as they provide large advantages in terms of expressive power. Despite the radical paradigm shift, their interaction model is firmly tied to the archetypal concept of strokes and gestures over a whiteboard. In this paper we introduce a novel pointing device that enables one to escape the surface-based interaction, by means of a robust and occlusion-resilient multi-camera 3D tracking. More precisely, we designed a frequency-based active pen. By means of a camera network such pen can be localized in a 3D frame featuring the same 5 degrees of freedom exposed by a real whiteboard marker. Our approach allows for using many pointers at the same time, by reliably assigning an unique and permanent identity to each one. By levering on these capabilities, interaction designers can conceive new and inventive interaction models. A few of them have been implemented within this study and are described in the experimental part of this work.